PENGARUH ERGONOMI KERJA TERHADAP RISIKO LOW BACK PAIN PADA PEKERJA DI INDONESIA - Nurhani Mazly Harahap; Abdul Rohim Tualeka; Hapsoro Agung Jatmiko (Media Gizi Kesmas, 2025)
Background: Occupational ergonomics is directly related to all work activities (both formal and informal) and focuses on the interaction between people and their work environment to reduce musculoskeletal injuries and improve worker well-being.   Objectives: The purpose of this study was to determine the impact of occupational ergonomics on the prevalence of low back pain among Indonesian workers aged 15–49 years. Methods: This study used secondary data from the Global Burden of Diseases (GBD) 2024, applying the Disability-Adjusted Life Years (DALYs) approach to measure the risk level of low back pain caused by occupational ergonomics. Results: The analysis revealed a substantial disparity in the burden of Low Back Pain (LBP) attributed to occupational ergonomics across provinces. West Java, East Java, and Central Java recorded the highest disease burden (DALYs). Meanwhile, the provinces with the highest ergonomic risk exposure levels (Summary Exposure Value/SEV) were North Maluku (29.48%), Maluku (29.27%), and East Nusa Tenggara (29.21%). North Kalimantan consistently showed the lowest exposure levels and disease burden. Conclusion: Workplace ergonomics substantially contributes to the burden of Low Back Pain (LBP) among workers. Large regional disparities (highest in Java and Maluku/NTT) underscore the need for more targeted health actions. Priority interventions should include strict regulation enforcement, workplace monitoring, and implementation of ergonomic solutions in high-risk industrial sectors to reduce DALYs.